Wheeze trajectories are modifiable through early‐life intervention and predict asthma in adolescence. Issue 6 (19th June 2018) - Owora, Arthur H.; Becker, Allan B.; Chan‐Yeung, Moira; Chan, Edmond S.; Chooniedass, Rishma; Ramsey, Clare; Watson, Wade T. A.; Azad, Meghan B.
Abstract: Background: The objectives of this study were to identify developmental trajectories of wheezing using data‐driven methodology, and to examine whether trajectory membership differentially impacts the effectiveness of primary preventive efforts that target modifiable asthma risk factors. Methods: Secondary analysis of the Canadian Asthma Primary Prevention Study (CAPPS), a multifaceted prenatal intervention among children at high risk of asthma, followed from birth to 15 years. Wheezing trajectories were identified by latent class growth analysis. Predictors, intervention effects, and asthma diagnoses were examined between and within trajectory groups. Results: Among 525 children, 3 wheeze trajectory groups were identified: Low‐Progressive (365, 69%), Early‐Transient (52, 10%), and Early‐Persistent (108, 21%). The study intervention was associated with lower odds of Early‐Transient and Early‐Persistent wheezing ( P < .01). Other predictors of wheeze trajectories included, maternal asthma, maternal education, city of residence, breastfeeding, household pets, infant sex and atopy at 12 months. The odds of an asthma diagnosis were three‐fold to six‐fold higher in the Early‐Persistent vs Low‐Progressive group at all follow‐up assessments ( P = .03), whereas Early‐Transient wheezing (limited to the first year) was not associated with asthma. In the Early‐Persistent group, the odds of wheezing were lower among intervention than control children (adjusted odds ratio: 0.67; 95% CI: 0.48; 0.93) at 7 years. Conclusions: Using data‐driven methodology, children can be classified into clinically meaningful wheeze trajectory groups that appear to be programmed by modifiable and non‐modifiable factors, and are useful for predicting asthma risk. Early‐life interventions can alter some wheeze trajectories (ie, Early‐Persistent) in infancy and reduce wheezing prevalence in mid‐childhood. Abstract :